2018
DOI: 10.1080/1068316x.2018.1503663
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the demographic and attitudinal predictors of rape myth acceptance in U.K. Police officers: developing an evidence-base for training and professional development

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 70 publications
3
27
0
2
Order By: Relevance
“…Moreover, studies comparing police officers to other populations, such as undergraduate students, find that overall levels of RMA do not significantly differ between groups, with both exhibiting low levels of acceptance (Sleath & Bull, 2017). A recent study (not included in the above review) conducted by Murphy and Hine (2018) found similarly low levels of rape myth acceptance in a large UK sample. Examination of specific myths has also highlighted that police officers in the UK tend to subscribe to 'she lied' myths to a greater extent than psychology and law students, while endorsing 'she asked for it' and 'he didn't mean to' myths to a lesser extent (Sleath & Bull, 2015).…”
Section: Rape Myth Acceptance In Police Officersmentioning
confidence: 94%
See 3 more Smart Citations
“…Moreover, studies comparing police officers to other populations, such as undergraduate students, find that overall levels of RMA do not significantly differ between groups, with both exhibiting low levels of acceptance (Sleath & Bull, 2017). A recent study (not included in the above review) conducted by Murphy and Hine (2018) found similarly low levels of rape myth acceptance in a large UK sample. Examination of specific myths has also highlighted that police officers in the UK tend to subscribe to 'she lied' myths to a greater extent than psychology and law students, while endorsing 'she asked for it' and 'he didn't mean to' myths to a lesser extent (Sleath & Bull, 2015).…”
Section: Rape Myth Acceptance In Police Officersmentioning
confidence: 94%
“…The present study therefore assessed the relationship between police officers' rape myth acceptance and their judgements of victim and perpetrator responsibility, as well as rape authenticity, in a large UK sample. This study represents a follow-up analysis to two previous studies assessing the attitudes and judgements of officers separately Hine, 2018, andMurphy, 2017 respectively). Specifically, this study assesses whether officers' judgements varied based on 'high' versus 'low' levels of rape myth acceptance, across hypothetical rape vignettes which varied on three specific rape myth-related factors: victim-perpetrator relationship, victim reputation, and initial point of resistance.…”
Section: The Present Studymentioning
confidence: 96%
See 2 more Smart Citations
“…Na prática, isso se traduz em constantes experiências de vitimização secundária por parte das vítimas e uma queda na probabilidade de que elas procurem ajuda (McMilla, 2015;Murphy & Hine, 2018). Por isso, para autores como Bueno e colegas (2016), faz-se mister que o currículo de policiais seja revisto, de modo a contemplar as especificidades da violência sexual e incluir temais tais quais: o acolhimento das vítimas e os encaminhamentos necessários.…”
unclassified